Method of two-scale decomposition of the solution of integro-differential equation with perturbation - Faizibaev , E. F.; Kadyrbekov , T. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
The solution of an integrodifferential equation with a small parameter is constructed by means of the two-variable expansion procedure. The obtained solutions of the van der Pol equation by the two-variable expansion method and the averaging method are compared. The obtained solutions coincide entirely to within quantities of second order of smallness.